The Effectiveness of Topic-Based Writing on EFL Learners’ Writing Skill - Nguyen Thi Dung (RIRAI Publisher, 2020)
Being accepted as out of the four essential language skills in the language learning process, writing seems to be difficult for numerous EFL learners. This research is an endeavor to explore if learners can grow out of the writing difficulties with topic-based writing activity. 78 third-year students at the Faculty of Foreign Languages of Phan Thiet University in Phan Thiet City, Binh Thuan Province participated in the study. These students were in the two writing classes, one class was treated as the experimental group (EG) and the other as the control group (CG). Research findings exposed the benefits of topic-based writing activity in nurturing learners' writing motivation and enhancing their writing skill. Furthermore, this activity gave students good chances to widen their knowledge on the topic, enrich their emotion on disadvantaged people, and build a friendly learning environment outside the classroom. The necessity and usefulness of the application of topic-based writing activity was predominantly recognized among students.